Children and youths' migration in a global landscape - Lee Atterberry, Adrienne; Garfield McCallum, Derrace; Tu, Siqi; Lutz, Amy (Sociological studies of children and youth ;, 2022)
This volume contains an Open Access Chapter Currently, there are more than 36 million transnationally mobile children and youth. Featuring the stories of children and youth from places such as Myanmar, India, Hungary, the USA, and Central America, Children and Youths' Migration in a Global Landscape interrogates how transnational mobility shapes the lives of the relatively young. This edited collection addresses questions that encourage us to consider what it means to be a transnationally mobile child or youth in the 21st century. How does transnational mobility affect youths' understanding of their ethnic identity? What is the link between educational attainment and social mobility? How does social class impact the educational trajectories of return migrant children? What impact does the knowledge economy have on new norms and practices related to human capital accumulation? Illustrating that transnationally mobile children and youths' experiences need social enquiry, this book pushes all of us to question our assumptions, challenge well-established theories, and rethink our understanding of the root causes of social inequality.